2018
DOI: 10.1021/acsami.8b06605
|View full text |Cite
|
Sign up to set email alerts
|

Modular Construction of Photoanodes with Covalently Bonded Ru- and Ir-Polypyridyl Visible Light Chromophores

Abstract: 1,10-phenanthroline is grafted to indium tin oxide (ITO) and titanium dioxide nanoparticle (TiO) semiconductors by electroreduction of 5-diazo-1,10-phenanthroline in 0.1 M HSO. The lower and upper potential limits (-0.20 and 0.15 V, respectively) were set to avoid reduction and oxidation of the 1,10-phenanthroline (phen) covalently grafted at C5 to the semiconductor. The resulting semiconductor-phen ligand (ITO-phen or TiO-phen) was air stable, and was bonded to Ru- or Ir- by reaction with cis-[Ru(bpy)(CHCN)] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 70 publications
0
28
0
Order By: Relevance
“…the MeCN ligands in [Ru(bpy) 2 (MeCN) 2 ](OTf) 2 . 263 The method has been successfully used for the grafting of Mn, 264,265 Fe, [265][266][267][268][269] Co, 262,265 Ni, 265,270,271 Cu, 160,272,273 Zn, 103 Ru, 103,263,274,275 Rh 153,276 and Ir 263 complexes. Most of the corresponding ligands were anchored following two different approaches; namely, the direct reduction of their diazonium precursors or the reaction of the conveniently modified ligand, (through one of the other post-functionalization processes examined in this review), with a previously immobilized organic coating.…”
Section: Coordination Bondingmentioning
confidence: 99%
See 2 more Smart Citations
“…the MeCN ligands in [Ru(bpy) 2 (MeCN) 2 ](OTf) 2 . 263 The method has been successfully used for the grafting of Mn, 264,265 Fe, [265][266][267][268][269] Co, 262,265 Ni, 265,270,271 Cu, 160,272,273 Zn, 103 Ru, 103,263,274,275 Rh 153,276 and Ir 263 complexes. Most of the corresponding ligands were anchored following two different approaches; namely, the direct reduction of their diazonium precursors or the reaction of the conveniently modified ligand, (through one of the other post-functionalization processes examined in this review), with a previously immobilized organic coating.…”
Section: Coordination Bondingmentioning
confidence: 99%
“…16). 262,263,[265][266][267]271,[274][275][276][277][278][279][280][281] However, these compounds are generally prepared ''in situ'' from diazotization of their amine precursors, as the diazonium species are only stable at low temperature (E0 1C) in the timescale of minutes, preventing their isolation. On the other hand, in some cases, it is convenient to include an alkyl chain as spacer between the coordination moiety of the ligand and the anchoring group.…”
Section: Coordination Bondingmentioning
confidence: 99%
See 1 more Smart Citation
“…[38] Further studies demonstrated similarly high stabilities of such electrografted interfaces on tin-doped indium oxide (ITO), fluorine-doped tin oxide (FTO) and TiO 2 . [37,[39][40][41] The reactive aryl radicals, formed during electrografting, tend, however, to react with already-grafted species, resulting in the deposition of polymeric, branched interfaces that do not facilitate DET with, e. g., large redox enzymes. Unlike small molecules, enzymes cannot penetrate such structures.…”
Section: Introductionmentioning
confidence: 99%
“…), oxides (ITO, TiO2, SnO2, SiO2, etc), and even insulating (glass, PMMA, PET, PP, etc.) substrates, being either massive, flat surfaces or nanomaterials, 5,6 and iii) the high diversity of diazonium salts that can be used (para-substituted aryl derivatives, 4,5 porphyrins, [7][8][9][10] calixarenes, [11][12][13][14][15][16][17][18][19][20] pyridine, 21,22 polyoxometalates, 23 transition metal complexes, [24][25][26][27] biomolecules, 28-30 etc). The grafting of diazonium salts has raised academic interest in various fields such as sensing, catalysis, anticorrosion, anti(bio-)fouling, molecular electronics.…”
Section: Introduction and Overviewmentioning
confidence: 99%